Sociological Foundation of Pancasila Education as the Original Identity of Indonesian Society - Aris Saputro (Universitas of Muhammadiyah Makassar, 2021)
Abstract. The purpose of writing this article is to understand the sociological foundation of Pancasila education as the original identity of Indonesian society. A sociological foundation is a foundation that relies on the interaction between individuals with fundamental values in society. Pancasila is described as the norm of ethics because based on Pancasila are moral values. This type of research uses qualitative description. The results of the discussion on the sociological basis of Pancasila education as the original identity of Indonesian society is the basis of a basic or focused explanation contained on an aspect of social sciences that teaches about the values of Pancasila that live and develop in local wisdom customs in Indonesia. Conclusion The sociological foundation of Pancasila as the traditional identity of Indonesian society is Pancasila a formulation of values rooted in the value of values contained and derived from various values in the ethnic group in Indonesia.Keywords: Sociology Foundation; Pancasila Education; Indigenous Tradition IdentityAbstrak. Tujuan dari penulisan artikel ini adalah memahami landasan sosiologis pendidikan Pancasila sebagai identitas asli masyarakat Indonesia. Landasan sosiologis merupakan landasan yang bertumpu pada interaksi antar individu satu dengan lainnya dengan nilai-nilai yang fundamental dalam masyarakat. Pancasila dijabarkan sebagai norma etik karena pada dasar Pancasila adalah nilai-nilai moral. Jenis Penelitian ini menggunakan deskripstif kualitatif. Hasil pembahasan pada landasan sosiologis pendidikan Pancasila sebagai identitas asli masyarakat Indonesia yaitu landasan sebuah dasar atau tumpuan penjelasan yang terkandung mengenai suatu aspek ilmu sosial yang mengajarkan tentang nilai-nilai pada Pancasila yang hidup dan berkembang dalam kearifan lokal adat istiadat di Indonesia. Kesimpulan Landasan sosiologis yang berjiwa Pancasila sebagai identitas tradisi masyarakat Indonesia adalah Pancasila sebuah rumusan nilai-nilai yang berakar dalam penghayatan nilai yang terkandung dan berasal dari berbagai nilai pada suku bangsa di Indonesia.Kata Kunci: Landasan Sosiologi; Pendidikan Pancasila; Identitas Tradisi Masyarakat Asli